Prevalence of Short Dental Roots in Four Ethnic Groups in an Orthodontic Population - Kathryn Edgcomb; Ellen BeGole; Carla Evans; Bradford Johnson; Xianghong Luan (Dental Anthropology Association, 2011)
The purpose of the current study was to investigate if a significant relationship exists between ethnicity, sex, and short dental roots. The hypotheses are: 1. Hispanics have a higher prevalence of short dental roots than Caucasians, African Americans, and Asians; and 2. Females have a higher prevalence of short dental roots than males. The experimental groups consisted of 30 Caucasians, 30 Hispanics, 30 African Americans, and 26 Asian subjects who presented to University of Illinois Department of Orthodontics for treatment. Actual root length (mm) and relative root length were measured on periapical radiographs, for the maxillary and mandibular central and lateral incisors, and second premolars. The results showed that Asians had the shortest dental root lengths for all teeth measured, except the maxillary second premolar. Significant differences in relative root length values between the ethnic groups were found for the maxillary central incisor and second premolar. Females had shorter roots than their male counterparts within each ethnic group.